A comparative study of the accumulation of trace elements in Brassicaceae plant species with phytoremediation potential. (September 2019) - Drozdova, Irina; Alekseeva-Popova, Natalya; Dorofeyev, Vladimir; Bech, Jaume; Belyaeva, Alla; Roca, Núria
Abstract: Native plant species growing on contaminated sites in an urban environment successfully develop under strong anthropogenic pressure and thereby may have the potential for phytoremediation. The concentrations of potentially toxic metals were measured in leaves, roots, stems, and inflorescences of fifteen Brassicaceae plant species from the urban park of Botanical Garden of Komarov Botanical Institute. The potential of phytoextraction and phytostabilization of the species was evaluated considering the concentration of Cd, Cu, Ni, Pb, Zn in the plant organs, and the bioconcentration factor (BCF) and the translocation factor (TF). The metal content in plant organs varied with plant species. The study of metal accumulation in plants showed that Brassica campestris has the potential for the simultaneous phytoextraction of three metals Zn, Cd, and Cu, and Rorippa palustris – of two metals Zn and Cd. According to received data, species Sinapis arvensis and Thlaspi arvense can be considered adequate candidates for soil Zn and Pb phytostabilization and soil conservation. Highlights: Brassicaceae species have the ability to develop successfully under strong anthropogenic pressure. These species are accumulated high concentrations potentially toxic metals in their organs. Brassica campestris has the potential for the simultaneous phytoextraction of Zn, Cd, and Cu. Rorippa palustris should be used in phytoextraction of Zn and Cd. Sinapis arvensis and Thlaspi arvense – adequate candidates for soil Zn and Pb phytostabilization.